A preliminary study of a sediment core drilled from the mud area on the inner shelf of the East China Sea: Implications for paleoclimatic changes during the fast transgression period (13 ka B.P.–8 ka B.P.). (16th June 2017) - Liu, Shengfa; Mi, Beibei; Fang, Xisheng; Li, Xiaoyan; Pan, Hui-Juan; Chen, Min-Te; Shi, Xuefa
Abstract: A 35.30 m-long core (MZ02) that was recovered from a water depth of 32.4 m from the inner shelf mud deposit of the East China Sea is analyzed to determine its sedimentary characteristics, color reflectance, clay mineral content, element geochemistry components and AMS 14 C dating to investigate the sedimentation rate, sediment provenance and paleoclimate evolution during the fast transgression period. Rare earth element and clay mineral proxies indicate that mixed-provenance sediment accumulated in the foreshore–nearshore region at the beginning of the fast transgression period, with a higher sedimentation rate of 5.58 m/ka. From the early Holocene (9.8–9.5 ka B.P.), the sedimentation rate declined by approximately 1.73 m/ka, and the sediment provenance obviously changed. The silt fraction resembled that of Taiwan's mountainous rivers and the clay fraction was primarily transported from the Yangtze River. A multiple proxy system including sediment redness (a*), chemical index of alteration (CIA), clay mineral ratio (smectite/kaolinite), and major and trace element ratios (CaO/MgO, Ba/Sr), also provides a good paleoclimate record during the fast transgression period, which can be divided into three units. All the proxies barely changed during Unit I (12.88–10.85 ka B.P.), revealing that the climate remained relatively stable. Obvious fluctuations occurred during Unit II (10.85–10.05 ka B.P.), and the temperature kept decreasing for more than 1 ka until the Younger Dryas event, showing a notable regional response to global climate changes. A continuous warming trend resumed again during Unit III (10.05–8.15 ka B.P.), which may mark the threshold of the Holocene warm period. In addition, we find significant 80-yr, 89-yr and 100-yr cycles in the CIA, CaO/MgO and Ba/Sr records, which imply the possible influence of solar activity on regional climate change during the fast transgression period in the Asian margin region.